Cost and outcomes associated with participating in the Community Fireguard Program : Experiences from the Black Saturday bushfires in Victoria, Australia. (September 2015) - Gibbs, L.; Sia, K-L.; Block, K.; Baker, E.; Nelsson, C.; Gilbert, J.; Cook, A.; MacDougall, C.
Abstract: There is increasing recognition of the importance of shared responsibility between community and government in supporting community preparedness in disaster risk reduction programs. However, there is limited evidence to support decision making about how best to allocate resources. This paper presents an economic analysis of the Community Fireguard Program coordinated by the Country Fire Authority in Victoria, Australia. The economic analysis evaluates the costs and benefits of the Community Fireguard program (estimated in 2012 Australian dollars) to determine the efficiency of the program in terms of its outcomes of loss of life and property loss in the event of a bushfire. We take a societal perspective, including all costs and benefits regardless of who bears the costs, who receives the benefits or who provides the resources. The analysis uses data from a previous review of the program and estimates of costs and benefits over ten years, assuming each region faces a 10-year risk of major bushfire and the CFG group learnings would last ten years. Totalled over ten years, the cost per Fireguard Group for the program is 10, 884, with a range of 2697–19, 071, and in the event of a major bushfire the predicted savings from reduced property loss is 732, 747 and from reduced fatality 1.4 million. Even if the risk of major bushfire event in a region were one in 100 years, the estimated cost savings in a 100-year period is 217, 116 per group. The value of the psychosocial impacts was not calculated, as quantitative data are currently not available.